Adolescents' Quality of Life and Mental Health Needs during the Initial Phase in a Closed Institution. Issue 2 (3rd April 2022) - Van Hecke, Nele; Meulewaeter, Florien; Rowaert, Sara; Nieuwenhuizen, Chijs van; Van Damme, Lore; Vanderplasschen, Wouter; Vandevelde, Stijn
Abstract: This study investigated adolescents' Quality of Life and mental health needs during the first weeks in a closed institution for mandatory care and treatment to inform (gender-specific) rehabilitation. Questionnaires concerning socio-demographic variables, Quality of Life and mental health needs were administered (n  =  182; 90 boys and 92 girls; mean age = 16.2). Given the high prevalence of mental health needs in this study population and their significant negative correlation with QoL, we argue for a holistic view on rehabilitation and to broaden treatment aims in youth forensic care by including not only determinants of recidivism but also determinants of QoL.